PDA / TA / FeOOH-PVDF self-cleaning membrane as well as preparation method and application thereof
By repairing dopamine and tannic acid on PVDF membranes and mineralized Feooh in situ, PDA/TA/Feooh-PVDF self-cleansing film is prepared, solving the problem of low PVDF membrane hydrophilicity and easy pollution, and realized the volatile oil of Chinese medicine High -efficiency separation and long life of the membrane.
Patent Information
- Application Number
- CN202411645690.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-28
AI Technical Summary
PVDF membrane has low hydrophilicity and is easily contaminated, resulting in low separation efficiency and short service life, limiting its application in the separation of volatile oils of traditional Chinese medicine.
By mineralized FEOOH, which is modified on PVDF membranes modified in dopamine and tannin (TA), PDA/TA/Feooh-PVDF self-cleansing film is prepared to enhance the hydrophilicity and anti-pollution performance of the membrane.
It improves the separation efficiency of volatile oil of traditional Chinese medicine, extends the service life of the membrane, reduces operating costs, and achieves super -intimate water properties and self -cleaning properties.
Smart Images

Figure CN119368008A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane materials and relates to a PDA / TA / FeOOH-PVDF self-cleaning membrane and a preparation method and application thereof. Background Art
[0002] Today, the Chinese medicine industry is developing rapidly in China. Essential oils are important bioactive ingredients in Chinese medicines and have a wide range of biological activities, including antibacterial, antiviral, anti-inflammatory and antioxidant properties. However, the essential oils used in Chinese medicines (also known as Chinese medicine volatile oils) are generally volatile and unstable. When exposed to light, heat and air, the essential oils are easily decomposed, which brings great challenges to the effective extraction of essential oils. At present, there are distillation, solvent extraction, gas extraction and supercritical fluid extraction methods for essential oil extraction. Steam distillation (SD) is the most commonly used method for Chinese medicine volatile oils because it does not require organic solvents and preserves the integrity of the raw material components. It inherits the traditional Chinese medicine method of decoction and fully reflects the integrity, safety and effectiveness of Chinese medicine. However, due to the special properties of volatile oils, they are easy to volatilize and lose, oxidize and deteriorate. The separation and purification of volatile oils by vacuum distillation, chromatographic separation and other methods are often not suitable for large-scale application in industrial production. Therefore, it is urgent to develop an efficient, environmentally friendly and safe technology for separating essential oils from water to effectively deal with these challenges.
[0003] As one of the most promising separation technologies, membrane separation technology is mainly used to separate, enrich, concentrate and purify solutes in wastewater. Due to its low energy consumption, small footprint, simple operation and high efficiency, it has become an important means of treating chemical wastewater such as oily wastewater and pharmaceutical wastewater. The simplification and separation of oil-water emulsions by membrane technology is an important progress in the application of membrane separation technology in the separation of volatile oil and water in traditional Chinese medicine.
[0004] In membrane separation technology, the performance of membrane materials plays a decisive role in separation efficiency. The most widely used membrane materials include organic polymer membrane materials such as cellulose acetate, aromatic polyamide, polyether sulfone and fluoropolymer, among which polyvinylidene fluoride membrane (PVDF membrane) is widely used in water treatment, food processing, biomedicine and other fields because of its excellent oxidation resistance, thermal stability, mechanical properties, chemical corrosion resistance, hydrolysis resistance and easy film formation. However, due to the low surface energy of PVDF membrane, good hydrophobicity, but low hydrophilicity, proteins and microorganisms in water are easily adsorbed and deposited on the surface or inside of the membrane, which easily causes membrane pollution, making the pores of PVDF membrane gradually shrink or blocked, greatly reducing the utilization rate of PVDF membrane, not only reducing the separation efficiency of PVDF membrane to volatile oil of traditional Chinese medicine, but also shortening the service life of PVDF membrane, increasing operating costs, and greatly restricting the application of PVDF membrane. Summary of the invention
[0005] In view of the technical problems that the above-mentioned PVDF membrane has low hydrophilicity, is easily contaminated and has low separation efficiency, the present invention provides a PDA / TA / FeOOH-PVDF self-cleaning membrane and a preparation method and application thereof.
[0006] The invention prepares a PDA / TA / FeOOH-PVDF self-cleaning membrane by in-situ mineralization of FeOOH on a PVDF membrane modified with dopamine PDA and TA, thereby solving the technical problems that PVDF has low hydrophilicity and is easily contaminated. The prepared self-cleaning membrane is used in the separation of volatile oils of traditional Chinese medicine and has excellent separation efficiency.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a PDA / TA / FeOOH-PVDF self-cleaning membrane comprises the following steps:
[0009] Step 1: Membrane pretreatment
[0010] The polyvinylidene fluoride membrane is pretreated by immersion to obtain a pretreated PVDF membrane;
[0011] Step 2: Membrane modification
[0012] Dopamine hydrochloride is dissolved in a Tris-HCl solution, and then FeCl3·6H2O and tannic acid are added to prepare a solution, and the pretreated PVDF membrane in step 1 is placed in the solution, and mixed evenly to obtain a PDA / TA / Fe(III)-PVDF membrane; the volume mass ratio of the dopamine hydrochloride, Tris-HCl solution, FeCl3·6H2O, tannic acid and pretreated PVDF membrane is (0.1-0.5) g: (30-100) ml: (0.05-0.4) g: (0.05-0.4) g: (1.01-2.25) g; the concentration of tris(hydroxymethyl)aminomethane in the Tris-HCl solution is 0.01 mol / L-0.1 mol / L;
[0013] Step 3: In-situ mineralization
[0014] Dissolve FeCl3·6H2O in water, then add the PDA / TA / Fe(Ⅲ)-PVDF membrane in step 2 for in-situ mineralization to obtain PDA / TA / FeOOH-PVDF membrane; the mass ratio of FeCl3·6H2O, water and PDA / TA / Fe(Ⅲ)-PVDF membrane is (0.05-0.4):(30-50):(1.01-2.25).
[0015] It is further defined that in step 1, the soaking pretreatment is: soaking the polyvinylidene fluoride membrane in anhydrous ethanol for 1 hour to 12 hours.
[0016] It is further defined that in step 2, the Tris-HCl solution is prepared according to the following method: tris(hydroxymethyl)aminomethane is dissolved in water, and then the pH is adjusted to 7-11.5 with hydrochloric acid.
[0017] It is further defined that in step 2, the mixing is performed by shaking in a shaker for 6 hours to 24 hours.
[0018] It is further defined that in step three, the temperature of in-situ mineralization is 30°C to 80°C, and the time of in-situ mineralization is 12h to 24h.
[0019] A PDA / TA / FeOOH-PVDF self-cleaning membrane is prepared by using the method for preparing the PDA / TA / FeOOH-PVDF self-cleaning membrane.
[0020] It is further defined that the surface roughness Ra of the PDA / TA / FeOOH-PVDF self-cleaning membrane is at most 28.3, and the water contact angle is at most 24.51°.
[0021] The application of the PDA / TA / FeOOH-PVDF self-cleaning membrane in improving the separation efficiency of volatile oils from traditional Chinese medicines.
[0022] It is further defined that the Chinese medicine volatile oil includes one or more of clove oil, patchouli oil, star anise oil, nutmeg oil and bupleurum oil.
[0023] Compared with the prior art, the technical effects of the present invention are:
[0024] 1. The PDA / TA / FeOOH-PVDF self-cleaning membrane provided by the present invention utilizes three raw materials, namely PDA (polydopamine), TA (tannic acid) and inorganic iron mineral FeOOH, to modify the PVDF membrane. The abundant hydroxyl groups on the surfaces of PDA and TA can not only enhance the hydrophilicity of the PVDF membrane, but also have self-cleaning properties, and can form a hydration layer on the surface of the PVDF membrane to prevent oil from polluting the membrane.
[0025] 2. The PDA / TA / FeOOH-PVDF self-cleaning membrane prepared by the present invention can couple the photo-Fenton reaction and membrane separation technology, and exhibit rapid and strong self-cleaning properties, which can not only greatly improve the anti-pollution performance of the membrane; but also the surface roughness reaches up to 28.3, and the minimum water contact angle is 24.51°, showing super hydrophilicity, and can efficiently separate oil-water emulsions of different Chinese medicine volatile oils, improve the separation efficiency of Chinese medicine volatile oils, thereby extending the service life of the membrane and reducing costs.
[0026] 3. The separation efficiency of the modified PDA / TA / FeOOH-PVDF self-cleaning membrane of the present invention for different Chinese herbal volatile oil emulsions is greater than 90%, indicating that the self-cleaning membrane has excellent separation efficiency for Chinese herbal volatile oil.
[0027] 4. The PDA / TA / FeOOH-PVDF self-cleaning membrane of the present invention is an organic-inorganic composite membrane, which mineralizes FeOOH on the surface of the PVDF membrane modified by PDA and TA, thereby forming a chelating layer of PDA, TA and iron ions, providing active sites for the growth of the photo-Fenton catalyst, and will not change the crystal structure of FeOOH, which is beneficial to enhancing the stability of the membrane.
[0028] 5. The preparation method of the PDA / TA / FeOOH-PVDF self-cleaning membrane of the present invention is achieved through physical mixing, mechanical stirring and in-situ mineralization. The process is simple and fast, easy to implement, easy to control, low in cost, high in yield, and has good industrial prospects, and is suitable for popularization and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 ad is PVDF membrane and PDA-TA-FeOOH prepared in Example 2 0.2 / SEM images (surface and cross-section) and AFM images of PVDF membrane;
[0030] Figure 1 ej are PVDF membranes, control groups (FeOOH-PVDF, TA / FeOOH-PVDF, PDA / FeOOH-PVDF and PDA / TA-PVDF) and PDA-TA-FeOOH prepared in Example 2 0.2 Atomic force microscopy image of / PVDF membrane;
[0031] Figure 2 XRD spectra of PDA-TA-FeOOH / PVDF membranes prepared in Examples 1, 2, and 3;
[0032] Figure 3 The water contact angle diagrams of the PDA-TA-FeOOH / PVDF membranes prepared in Examples 1, 2, and 3;
[0033] Figure 4 is the water contact angle of the control group (FeOOH-PVDF, TA / FeOOH-PVDF, PDA / FeOOH-PVDF, and PDA / TA-PVDF membranes);
[0034] Figure 5 PDA-TA-FeOOH prepared in Example 1 0.1 / PVDF membrane flux and separation efficiency of different Chinese herbal volatile oil emulsions;
[0035] Figure 6 PDA-TA-FeOOH prepared in Example 2 0.2 / PVDF membrane flux and separation efficiency of different Chinese herbal volatile oil emulsions;
[0036] Figure 7 PDA-TA-FeOOH prepared in Example 3 0.3 / PVDF membrane flux and separation efficiency of different Chinese herbal volatile oil emulsions;
[0037] Figure 8 The flux and separation efficiency of the control group FeOOH-PVDF membrane for different Chinese medicine volatile oil emulsions;
[0038] Fig. 9 The flux and separation efficiency of the control group TA / FeOOH-PVDF membrane for different Chinese medicine volatile oil emulsions;
[0039] Fig.10 The flux and separation efficiency of the control group PDA / FeOOH-PVDF membrane for different Chinese medicine volatile oil emulsions;
[0040] Fig.11 The flux and separation efficiency of the control group PDA / TA-PVDF membrane for different Chinese medicine volatile oil emulsions;
[0041] Fig.12 PDA-TA-FeOOH prepared in Example 2 0.2 Flux and separation efficiency of PVA / PVDF membrane for patchouli oil emulsion after 10 cycles under photo-Fenton conditions. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The technical idea of the present invention is to develop a new type of PDA / TA / FeOOH-PVDF self-cleaning membrane by in-situ mineralization of FeOOH on a PVDF membrane modified with PDA and TA, thereby solving the problem that the existing PVDF membrane has low hydrophilicity and is easily contaminated, and thus can be used for the efficient separation of volatile oils from traditional Chinese medicines.
[0044] Dopamine hydrochloride is a natural biomass molecule that is easily oxidized and polymerized under alkaline conditions to generate PDA. The polymerization of PDA through covalent bonds and non-covalent pathways makes the PDA molecule have a large number of hydroxyl, amino, and imino functional groups. In addition, the large number of repeated catechol units in the PDA molecule have excellent adhesion properties, allowing PDA to be coated on almost all material surfaces.
[0045] Tannic acid (TA) is a natural polyphenol macromolecule extracted and purified from plants. It has strong pharmacological and biological activity and can react with metal ions.
[0046] FeOOH is a ubiquitous narrow-bandgap semiconductor that exhibits visible light response and stability in heterogeneous photocatalytic oxidation processes. In addition, FeOOH, as a Fenton reagent, has also attracted widespread attention due to its abundant resources, widespread presence in nature, relatively low cost, and wide effective pH range.
[0047] In the process of in-situ mineralization of FeOOH on a PVDF membrane modified by PDA and TA of the present invention, the hydroxyl groups contained in PDA and TA can not only enhance the hydrophilicity of the PVDF membrane, but also form a hydration layer on the surface of the PVDF membrane to prevent oil from polluting the membrane; FeOOH has chemical properties such as high surface charge and surface -OH content, large specific surface area, etc., and the introduction of the inorganic material FeOOH into the PVDF membrane can enhance its tensile and compressive resistance, and the hydroxyl groups on the FeOOH can improve the hydrophilicity of the membrane and then form an anti-pollution hydration layer on the membrane surface.
[0048] The preparation method of the PDA / TA / FeOOH-PVDF self-cleaning membrane provided by the present invention comprises the following steps:
[0049] Step 1: Membrane pretreatment
[0050] The polyvinylidene fluoride membrane is pretreated by immersion to obtain a pretreated PVDF membrane.
[0051] In step 1 of the present invention, the soaking pretreatment is: soaking the polyvinylidene fluoride membrane in anhydrous ethanol for 1 hour to 12 hours.
[0052] Preferably, the soaking time is 1 h, 3 h, 5 h, 8 h, 10 h or 12 h.
[0053] Step 2: Membrane modification
[0054] Dopamine hydrochloride was dissolved in Tris-HCl solution, and FeCl3·6H2O and tannic acid were added to prepare a solution, and the pretreated PVDF membrane in step 1 was placed in the solution and mixed evenly to obtain a PDA / TA / Fe(III)-PVDF membrane.
[0055] In step 2 of the present invention, the Tris-HCl solution is prepared according to the following method: tris(hydroxymethyl)aminomethane is dissolved in water, and then the pH is adjusted to 7-11.5 with hydrochloric acid.
[0056] Preferably, the concentration of tris(hydroxymethyl)aminomethane in the Tris-HCl solution is 0.01 mol / L to 0.1 mol / L, and the concentration of hydrochloric acid is 0.1 mol / L.
[0057] In step 2 of the present invention, the mixing is uniformly performed by shaking in a shaking table for 6 hours to 24 hours.
[0058] Preferably, the mixing is performed by shaking in a shaker for 6 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h, 22 h or 24 h.
[0059] In the present invention, the volume mass ratio of dopamine hydrochloride, Tris-HCl solution, FeCl3·6H2O, tannic acid and pretreated PVDF membrane is (0.1-0.5) g: (30-100) ml: (0.05-0.4) g: (0.05-0.4) g: (1.01-2.25) g.
[0060] Step 3: In-situ mineralization
[0061] FeCl3·6H2O was dissolved in water, and then added to the PDA / TA / Fe(III)-PVDF membrane in step 2 for in-situ mineralization to obtain the PDA / TA / FeOOH-PVDF membrane.
[0062] In the present invention, the mass ratio of FeCl3·6H2O, water and PDA / TA / Fe(III)-PVDF membrane is (0.05-0.4):(30-50):(1.01-2.25).
[0063] In step three of the present invention, the temperature of in-situ mineralization is 30° C. to 80° C., and the time of in-situ mineralization is 12 h to 24 h.
[0064] Preferably, the temperature of the in-situ mineralization is 30°C, 40°C, 50°C, 60°C, 70°C or 80°C, and the time of the in-situ mineralization is 12h, 15h, 18h, 20h, 22h or 24h.
[0065] The present invention uses the PDA / TA / FeOOH-PVDF self-cleaning membrane prepared by the preparation method to improve the separation efficiency of volatile oils of traditional Chinese medicine.
[0066] The technical solution protected by the present invention is described in detail below with several groups of embodiments.
[0067] It should be noted that, unless otherwise specified, the chemicals and reagents used in the following examples are all conventional market-purchased products in the art.
[0068] It should be noted that, unless otherwise specified, the operating steps used in the following embodiments are conventional existing operating methods in the art.
[0069] Example 1
[0070] In this example, FeOOH was in situ mineralized on a PVDF membrane modified with dopamine PDA and tannic acid TA, and the mass of FeCl3·6H2O added for in situ mineralization was 0.1 g.
[0071] The method for preparing the PDA / TA / FeOOH-PVDF self-cleaning membrane provided in this embodiment comprises the following steps:
[0072] Step 1: Membrane pretreatment
[0073] The polyvinylidene fluoride membrane was soaked in anhydrous ethanol for 1 hour to obtain a pretreated PVDF membrane.
[0074] Step 2: Membrane modification
[0075] 0.1 g of dopamine hydrochloride was dissolved in 50 ml of Tris-HCl solution, and 0.4 g of FeCl3·6H2O and 0.4 g of tannic acid TA were added to prepare a solution. 1.1061 g of pretreated PVDF membrane was put into the solution and mixed evenly on a shaker for 12 h to obtain a PDA / TA / Fe(III)-PVDF membrane.
[0076] In this embodiment, the Tris-HCl solution is prepared by dissolving 0.6055 g of tris(hydroxymethyl)aminomethane in 80 ml of distilled water, and adjusting the pH to 8.5 with 0.1 mol / L hydrochloric acid.
[0077] Step 3: In-situ mineralization
[0078] 0.1g FeCl3·6H2O was added to 50ml distilled water, and then 1.1067g PDA / TA / Fe(Ⅲ)-PVDF membrane was placed in the solution for in-situ mineralization at 60℃ for 24h to obtain PDA / TA / FeOOH 0.1 -PVDF self-cleaning membrane.
[0079] Example 2
[0080] In this example, FeOOH was in situ mineralized on a PVDF membrane modified with dopamine PDA and tannic acid TA, and the mass of FeCl3·6H2O added for in situ mineralization was 0.2 g.
[0081] The method for preparing the PDA / TA / FeOOH-PVDF self-cleaning membrane provided in this embodiment comprises the following steps:
[0082] Step 1: Membrane pretreatment
[0083] The polyvinylidene fluoride membrane was soaked in anhydrous ethanol for 1 hour to obtain a pretreated PVDF membrane.
[0084] Step 2: Membrane modification
[0085] 0.1 g dopamine hydrochloride was dissolved in 50 ml Tris-HCl solution, 0.4 g FeCl3·6H2O and 0.4 g TA were added to prepare a solution, 1.1086 g pretreated PVDF membrane was put into the solution, and the solution was shaken for 12 h to obtain PDA / TA / Fe(III)-PVDF membrane.
[0086] In this embodiment, the Tris-HCl solution is prepared by dissolving 0.6055 g of tris(hydroxymethyl)aminomethane in 80 ml of distilled water, and adjusting the pH to 8.5 with 0.1 mol / L hydrochloric acid.
[0087] Step 3: Membrane in situ mineralization
[0088] 0.2 g FeCl3·6H2O was added to 50 ml distilled water, and then 1.1184 g PDA / TA / Fe(Ⅲ)-PVDF membrane was placed in the solution for in-situ mineralization at 60°C for 24 h to obtain PDA / TA / FeOOH 0.2 -PVDF self-cleaning membrane.
[0089] Example 3
[0090] In this example, FeOOH was in situ mineralized on a PVDF membrane modified with dopamine PDA and tannic acid TA, and the mass of FeCl3·6H2O added for in situ mineralization was 0.3 g.
[0091] The method for preparing the PDA / TA / FeOOH-PVDF self-cleaning membrane provided in this embodiment comprises the following steps:
[0092] Step 1: Membrane pretreatment
[0093] The polyvinylidene fluoride membrane was soaked in anhydrous ethanol for 1 hour to obtain a pretreated PVDF membrane.
[0094] Step 2: Membrane modification
[0095] 0.1 g dopamine hydrochloride was dissolved in 50 ml Tris-HCl solution, 0.4 g FeCl3·6H2O and 0.4 g TA were added to prepare a solution, 1.1066 g pretreated PVDF membrane was put into the solution, and the solution was shaken for 12 h to obtain PDA / TA / Fe(III)-PVDF membrane.
[0096] In this embodiment, the Tris-HCl solution is prepared by dissolving 0.6055 g of tris(hydroxymethyl)aminomethane in 80 ml of distilled water, and adjusting the pH to 8.5 with 0.1 mol / L hydrochloric acid.
[0097] Step 3: Membrane in situ mineralization
[0098] 0.3 g FeCl3·6H2O was added to 50 ml distilled water, and then 1.1089 g PDA / TA / Fe(Ⅲ)-PVDF membrane was placed in the solution for in-situ mineralization at 60°C for 24 h to obtain PDA / TA / FeOOH 0.3 -PVDF self-cleaning membrane.
[0099] In order to verify the performance of the PDA / TA / FeOOH-PVDF self-cleaning membrane prepared in the above example, the following verification test was carried out.
[0100] In order to illustrate the performance advantages of the PDA / TA / FeOOH-PVDF self-cleaning membrane prepared by the present invention in the verification test, the following comparative examples were set for comparison.
[0101] Comparative Example 1: FeOOH-PVDF membrane
[0102] The preparation method of the FeOOH-PVDF membrane of this comparative example comprises the following steps:
[0103] Step 1: Membrane pretreatment
[0104] The polyvinylidene fluoride membrane was soaked in anhydrous ethanol for 1 hour to obtain a pretreated PVDF membrane.
[0105] Step 2: Membrane modification
[0106] 0.4 g FeCl3·6H2O was added to 50 ml Tris-HCl solution to prepare a solution, 1.1086 g pre-treated PVDF membrane was placed in the solution, and the solution was shaken for 12 hours to obtain Fe(III)-PVDF membrane. The preparation of Tris-HCl solution was referred to Example 2.
[0107] Step 3: Membrane in situ mineralization
[0108] 0.2 g of FeCl3·6H2O was added to 50 ml of distilled water, and then 1.1184 g of Fe(Ⅲ)-PVDF membrane was placed in the solution for in-situ mineralization at 60°C for 24 h to obtain FeOOH-PVDF membrane.
[0109] Comparative Example 2: TA / FeOOH-PVDF membrane
[0110] The preparation method of the TA / FeOOH-PVDF membrane of this comparative example comprises the following steps:
[0111] Step 1: Membrane pretreatment
[0112] The polyvinylidene fluoride membrane was soaked in anhydrous ethanol for 1 hour to obtain a pretreated PVDF membrane.
[0113] Step 2: Membrane modification
[0114] 0.4 g FeCl3·6H2O and 0.4 g TA were added to 50 ml Tris-HCl solution to prepare a solution, 1.1086 g pre-treated PVDF membrane was placed in the solution, and the solution was shaken for 12 hours to obtain TA / Fe(III)-PVDF membrane. The preparation of Tris-HCl solution was referred to Example 2.
[0115] Step 3: Membrane in situ mineralization
[0116] 0.2 g of FeCl3·6H2O was added to 50 ml of distilled water, and then 1.1184 g of TA / Fe(III)-PVDF membrane was placed in the solution for in-situ mineralization at 60°C for 24 h to obtain TA / FeOOH-PVDF membrane.
[0117] Comparative Example 3: PDA / FeOOH-PVDF membrane
[0118] The preparation method of the PDA / FeOOH-PVDF membrane of this comparative example comprises the following steps:
[0119] Step 1: Membrane pretreatment
[0120] The polyvinylidene fluoride membrane was soaked in anhydrous ethanol for 1 hour to obtain a pretreated PVDF membrane.
[0121] Step 2: Membrane modification
[0122] 0.1 g dopamine hydrochloride was dissolved in 50 ml Tris-HCl solution, and 0.4 g FeCl3·6H2O was added to prepare a solution, 1.1086 g pre-treated PVDF membrane was placed in the solution, and the PDA / Fe(III)-PVDF membrane was obtained by shaking for 12 hours. The preparation of Tris-HCl solution was referred to Example 2.
[0123] Step 3: Membrane in situ mineralization
[0124] 0.2 g of FeCl3·6H2O was added to 50 ml of distilled water, and then 1.1184 g of PDA / Fe(Ⅲ)-PVDF membrane was placed in the solution for in-situ mineralization at 60°C for 24 h to obtain PDA / FeOOH-PVDF membrane.
[0125] Comparative Example 4: PDA / TA-PVDF membrane
[0126] The preparation method of the FeOOH-PVDF membrane of this comparative example comprises the following steps:
[0127] Step 1: Membrane pretreatment
[0128] The polyvinylidene fluoride membrane was soaked in anhydrous ethanol for 1 hour to obtain a pretreated PVDF membrane.
[0129] Step 2: Membrane modification
[0130] 0.1 g dopamine hydrochloride was dissolved in 50 ml Tris-HCl solution, and 0.4 g TA was added to prepare a solution; 1.1086 g pre-treated PVDF membrane was placed in the solution, and shaken for 12 hours to obtain a PDA / TA / PVDF membrane. The preparation of the Tris-HCl solution was referred to Example 2.
[0131] Step 3: Membrane in situ mineralization
[0132] 1.1184 g of PDA / TA / PVDF membrane was placed in 50 ml of water and in-situ mineralized at 60°C for 24 h to obtain a PDA / TA / PVDF self-cleaning membrane.
[0133] The following test was carried out using the self-cleaning membranes prepared in Examples 1 to 3 and the membranes prepared in Comparative Examples 1 to 4 (control group) as samples.
[0134] Experiment 1: SEM test
[0135] Take the PVDF membrane and the PDA / TA / FeOOH prepared in Example 2 0.2 -PVDF self-cleaning membrane was tested by SEM. The results are as follows Figure 1 As shown, a and b are the surface and cross-sectional SEM images of PVDF at 100 nm and 50 μm, respectively; c and d are PDA / TA / FeOOH 0.2 -PVDF self-cleaning membrane surface and cross-sectional SEM images at 100 nm and 50 μm; e and j are PVDF, control group (FeOOH-PVDF membrane, TA / FeOOH-PVDF membrane, PDA / FeOOH-PVDF membrane and PDA / TA-PVDF membrane) and PDA / TA / FeOOH 0.2 -Atomic force microscopy image of PVDF self-cleaning membrane.
[0136] from Figure 1 From the SEM image, it can be seen that the surface of the PVDF membrane is smooth and porous ( Figure 1 Compared with the original PVDF membrane, the PDA / TA / FeOOH prepared in Example 2 0.2 -There are obvious nanoparticles attached to the surface of the PVDF self-cleaning membrane, and the cross section also shows that the load on the membrane penetrates into the cross section of the membrane and fills the pores ( Figure 1 (c and d).
[0137] from Figure 1It can also be seen in the figure: PVDF membrane, FeOOH-PVDF membrane, TA / FeOOH-PVDF membrane, PDA / FeOOH-PVDF membrane, PDA / TA-PVDF membrane and PDA / TA / FeOOH 0.2 -PVDF self-cleaning membrane surface roughness parameters Ra are 7.61, 10.2, 10.4, 10.8, 12.24 and 28.3 respectively. The self-cleaning membrane prepared by the present invention has a surface roughness much higher than that of the PVDF membrane and the control group (membranes prepared in Comparative Examples 1 to 4), and the increase in roughness is conducive to obtaining super hydrophilicity, indicating that the self-cleaning membrane prepared by the present invention has high hydrophilicity and can prevent secondary contamination of the membrane.
[0138] Experiment 2: XRD test
[0139] In this experiment, the PDA / TA / FeOOH-PVDF self-cleaning membranes prepared in Example 1, Example 2 and Example 3 were selected for XRD testing.
[0140] In this experiment, the XRD patterns of the three self-cleaning membranes are as follows: Figure 2 shown.
[0141] See also Figure 2 In addition to the characteristic peaks of PVDF membrane, diffraction peaks at 17.905°(002), 27.7699°(301), 31.703°(221) and 37.280°(104) were identified as FeOOH (JCPDS No. 220353). This indicates that FeOOH nanoparticles are successfully mineralized on the surface of PVDF membrane, verifying the feasibility of the preparation method of the present invention.
[0142] Test 3: Water contact angle test
[0143] In this experiment, the original PVDF membrane, the control group (membranes prepared in comparative examples 1 to 4), and the self-cleaning membranes prepared in examples 1, 2 and 3 were selected for water contact angle test.
[0144] In this test, the water contact angle results of the above films are as follows Figure 3 , 4 shown.
[0145] from Figure 3 It can be seen that the water contact angle of the original PVDF membrane is 76.67°; the water contact angles of the self-cleaning membranes prepared in different mass ratios in Example 1, Example 2 and Example 3 are 28.65°, 27.45° and 29.33° respectively; Figure 4It can be seen that the water contact angles of the four membranes of the control group, FeOOH-PVDF membrane, TA / FeOOH-PVDF membrane, PDA / FeOOH-PVDF membrane and PDA / TA-PVDF membrane, are 40.54, 38.56°, 37.64° and 36.77° respectively. By comparison, it can be seen that the contact angles of the self-cleaning membranes prepared in different mass ratios in Examples 1, 2 and 3 are reduced compared to the original PVDF membrane and the membrane of the control group. The results of this experiment show that the modified self-cleaning membrane has good hydrophilicity, thereby forming a hydration layer on the surface of the PVDF membrane to prevent oil from contaminating the membrane and having self-cleaning properties.
[0146] Experiment 4: Flux and separation efficiency of different Chinese herbal volatile oil emulsions
[0147] In this experiment, the PDA / TA / FeOOH-PVDF self-cleaning membranes prepared in Example 1, Example 2 and Example 3 and the control group (FeOOH-PVDF membranes, TA / FeOOH-PVDF membranes, PDA / FeOOH-PVDF membranes and PDA / TA-PVDF membranes prepared in Comparative Examples 1 to 4) were selected for flux and separation efficiency performance tests.
[0148] The test process is: mix Chinese herbal volatile oil, water (oil: water 1:99), and Tween-80 (10 mg), treat with an ultrasonic machine at 25°C for 30 minutes, and mechanically stir for 12 hours to obtain a stable water-in-oil Chinese herbal volatile oil emulsion.
[0149] The five volatile oils of traditional Chinese medicine used in this experiment are patchouli oil, clove oil, star anise oil, nutmeg oil and Bupleurum chuinese oil.
[0150] The oil-water separation test used a customized membrane filtration device (Amicon Stirred Cell, UFSC40001) to evaluate the membrane flux. The device consists of an ultrafiltration membrane cup, a nitrogen bottle, a flow meter, a digital balancer, a feed liquid bottle, and a permeable water reservoir. The filtration membrane area is 41.8 cm 2 , the external pressure was set to 0.1 MPa. Before the measurement, a nitrogen bottle was used to pre-pressurize the membrane at a pressure of 1.5 bar for 1 h to allow the membrane to reach a stable state, and then the prepared water-in-oil Chinese medicine volatile oil emulsion was tested for 1 h flux and separation efficiency using a membrane device.
[0151] The flux J was calculated according to the following formula: w :
[0152]
[0153] Where: J w is the flux, unit L·m -2 ·h -1 bar -1 ; V is the volume of permeate water, unit L; A is the effective membrane area, unit m 2 ; ΔT is the operation time, unit is h; ΔP is the transmembrane pressure, unit is bar.
[0154] The oil content before and after filtration was measured using a COD meter (JC-2017), and the separation efficiency R (%) was calculated according to the following formula:
[0155]
[0156] Where: COD1 is the oil content in the filtrate, COD0 is the oil content in the water-in-oil emulsion.
[0157] The results of the flux and separation efficiency of the above five Chinese herbal volatile oils separated by Examples 1 to 3 and the control group are shown in Figure 5 to Figure 11 And Table 1. Figure 5 PDA-TA-FeOOH prepared in Example 1 0.1 Flux and separation efficiency of PVDF self-cleaning membrane for different Chinese herbal volatile oil emulsions, Figure 6 PDA-TA-FeOOH prepared in Example 2 0.2 Flux and separation efficiency of PVDF self-cleaning membrane for different Chinese herbal volatile oil emulsions, Figure 7 PDA-TA-FeOOH prepared in Example 3 0.3 Flux and separation efficiency of PVDF self-cleaning membrane for different Chinese herbal volatile oil emulsions, Figure 8-Figure 11 The flux and separation efficiency of different Chinese medicine volatile oil emulsions of the control groups (control 1 is FeOOH-PVDF membrane, control 2 is TA / FeOOH-PVDF membrane, control 3 is PDA / FeOOH-PVDF membrane, and control 4 is PDA / TA-PVDF membrane) are shown in order.
[0158] Table 1 Flux and separation efficiency of different membranes for volatile oils of traditional Chinese medicine
[0159]
[0160] Note: In Table 1, the unit of flux is L·m -2 ·h -1 bar -1 , the unit of separation efficiency is %.
[0161] from Figure 5 to Figure 7As can be seen from Table 1, the three self-cleaning membranes prepared in Examples 1 to 3 have a separation efficiency of more than 90% for different Chinese medicine volatile oil emulsions, and the self-cleaning membrane prepared in Example 2 has a better separation effect for the five Chinese medicine volatile oils. Figure 8 to Figure 11 As can be seen from Table 1, the separation efficiency of the four control groups for different Chinese medicine volatile oil emulsions is less than 90%, indicating that the self-cleaning membrane prepared by the present invention has a high separation efficiency for Chinese medicine volatile oil.
[0162] from Figure 5 to Figure 11 As can be seen from Table 1, the fluxes of Examples 1 to 3 for each Chinese medicine volatile oil are greater than the fluxes of the four control groups for Chinese medicine volatile oil, indicating that the self-cleaning membrane prepared by the present invention has a larger flux in the separation of Chinese medicine volatile oil, which is beneficial to the separation of Chinese medicine volatile oil.
[0163] In summary, compared with the control groups, the dopamine hydrochloride used in the present invention is easily oxidized and polymerized under alkaline conditions to generate PDA, and then the PVDF membrane is modified using three raw materials, PDA (polydopamine), TA (tannic acid) and inorganic iron mineral FeOOH, to obtain a self-cleaning membrane. The raw materials act synergistically under the preparation conditions of the present invention to promote the separation of volatile oils from traditional Chinese medicine.
[0164] In addition, in this experiment, a self-cleaning membrane was used to separate a single component of Chinese herbal volatile oil. When a mixed Chinese herbal volatile oil is formed by multiple components, a higher separation effect can also be achieved by using a self-cleaning membrane.
[0165] Test 5: Stability and anti-pollution performance
[0166] In this experiment, PDA / TA / FeOOH prepared in Example 2 was selected. 0.2 -PVDF self-cleaning membrane was tested for stability and anti-fouling performance.
[0167] Fig.12 PDA / TA / FeOOH prepared in Example 2 0.2 -PVDF self-cleaning membrane repeatedly separated the patchouli perfume oil emulsion under the photo-Fenton condition. The results showed that after 10 times of repeated use, the separation efficiency and flux did not decrease significantly, proving that the self-cleaning membrane prepared in Example 2 of the present invention has good stability and anti-fouling performance.
[0168] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a PDA / TA / FeOOH-PVDF self-cleaning membrane, characterized in that: The following steps are involved: Step 1: Membrane pretreatment The polyvinylidene fluoride membrane is pretreated by immersion to obtain a pretreated PVDF membrane; Step 2: Membrane modification Dissolve dopamine hydrochloride in Tris-HCl solution, then add FeCl3·6H2O and tannic acid to prepare a solution, put the pretreated PVDF membrane in step 1 into the solution, mix well to obtain PDA / TA / Fe(III)-PVDF membrane; The volume mass ratio of dopamine hydrochloride, Tris-HCl solution, FeCl3·6H2O, tannic acid and pretreated PVDF membrane is (0.1-0.5) g: (30-100) ml: (0.05-0.4) g: (0.05-0.4) g: (1.01-2.25) g; the concentration of tris(hydroxymethyl)aminomethane in the Tris-HCl solution is 0.01 mol / L-0.1 mol / L; Step 3: In-situ mineralization Dissolve FeCl3·6H2O in water, then add the PDA / TA / Fe(Ⅲ)-PVDF membrane in step 2 for in-situ mineralization to obtain PDA / TA / FeOOH-PVDF membrane; the mass ratio of FeCl3·6H2O, water and PDA / TA / Fe(Ⅲ)-PVDF membrane is (0.05-0.4):(30-50):(1.01-2.25).
2. The method for preparing the PDA / TA / FeOOH-PVDF self-cleaning membrane according to claim 1, characterized in that: In the step 1, the soaking pretreatment is to soak the polyvinylidene fluoride membrane in anhydrous ethanol for 1 hour to 12 hours.
3. The method for preparing the PDA / TA / FeOOH-PVDF self-cleaning membrane according to claim 1, characterized in that: In the step 2, the Tris-HCl solution is prepared according to the following method: dissolving tris(hydroxymethyl)aminomethane in water, and then adjusting the pH value to 7-11.5 with hydrochloric acid.
4. The method for preparing the PDA / TA / FeOOH-PVDF self-cleaning membrane according to claim 1, characterized in that: In the step 2, the mixing is performed by shaking in a shaker for 6 hours to 24 hours.
5. The method for preparing the PDA / TA / FeOOH-PVDF self-cleaning membrane according to claim 1, characterized in that: In the step 3, the temperature of the in-situ mineralization is 30° C. to 80° C., and the time of the in-situ mineralization is 12 h to 24 h.
6. A PDA / TA / FeOOH-PVDF self-cleaning membrane prepared by the method for preparing a PDA / TA / FeOOH-PVDF self-cleaning membrane according to claim 1.
7. The PDA / TA / FeOOH-PVDF self-cleaning membrane according to claim 6, characterized in that: The surface roughness Ra of the PDA / TA / FeOOH-PVDF self-cleaning membrane is as high as 28.3, and the water contact angle is as low as 24.51°.
8. Application of the PDA / TA / FeOOH-PVDF self-cleaning membrane as claimed in claim 6 in improving the separation efficiency of volatile oils from traditional Chinese medicines.
9. The use according to claim 8, characterized in that: The traditional Chinese medicine volatile oil includes one or more of clove oil, patchouli oil, star anise oil, nutmeg oil and bupleurum oil.
Citation Information
Cited By
Composite membrane material for oil-water separation as well as preparation method and application of composite membrane material
CN119896980A
Inorganic hydrogel / polyvinylidene fluoride oil-water separation membrane as well as preparation method and application thereof
CN120155087A